2001
DOI: 10.1046/j.1444-2906.2001.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tropomyosin as a major allergen in the octopus Octopus vulgaris and elucidation of its IgE-binding epitopes

Abstract: The major allergen (named Oct v 1) in the muscle of the octopus Octopus vulgaris was purified by gel filtration on Sephacryl S‐300, anion‐exchange fast protein liquid chromatography on Mono Q and reverse‐phase high‐pressure liquid chromatography on TSKgel Octadecyl‐4PW. In addition to the molecular mass, amino acid composition and cross‐reactivity with Tur c 1 (turban shell Turbo cornutus allergen), the determined partial amino acid sequence clearly demonstrated that Oct v 1 is tropomyosin, similar to the know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Such aquatic food products are typically commercialised fresh, frozen or dried-salted, both at the artisan and industrial scales [18]. Previous compositional analyses on octopus have focused only on the investigation of phospholipids (PL) [19], collagen [20] and tropomyosin [21]. However, and due to increasing consumer demand, research scientists are paying more attention to this aquatic food product, especially to its growth patterns and to the effects of its sexual maturation on biochemical and compositional changes affecting food quality [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Such aquatic food products are typically commercialised fresh, frozen or dried-salted, both at the artisan and industrial scales [18]. Previous compositional analyses on octopus have focused only on the investigation of phospholipids (PL) [19], collagen [20] and tropomyosin [21]. However, and due to increasing consumer demand, research scientists are paying more attention to this aquatic food product, especially to its growth patterns and to the effects of its sexual maturation on biochemical and compositional changes affecting food quality [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…So far, tropomyosin has been established at the molecular level as the major allergen of a number of crustaceans including shrimp [1,2,3,4], crayfish [5], lobster [5], hermit crab [4], crab [4, 6] and barnacle [7]. In addition, tropomyosin has also been identified as the major allergen of mollusks such as cephalopods [8,9,10], gastropods [11, 12] and bivalves [12] and as one of the allergens of house dust mites [13, 14] and cockroaches [15, 16]. Thus, it is currently accepted that tropomyosin is a cross-reactive panallergen of invertebrates [15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…These peptides, excluding trypsin-cutting sites, were only part of the intact epitopes, and they also highly overlapped with previously reported allergenic shrimp TM epitopes. 17,29,30 Our previous studies also showed that the digestion products of TM still maintained the ability of sensitization. 35,36,43,44 This was the reason that TM had the ability to activate an allergic reaction after gastrointestinal digestion.…”
Section: ■ Discussionmentioning
confidence: 76%